Perilaku Cyberbullying pada Remaja dan Kaitannya dengan Kontrol Diri dan Komunikasi Orang Tua - Zahro Malihah; Alfiasari Alfiasari (Jurnal Ilmu Keluarga dan Konsumen, 2018)
The increasing of internet using among children and adolescents increases the risk of cyberbullying phenomenon. Therefore, it is needed to conduct a study to further analyze the phenomenon of cyberbullying in Indonesia; especially in order to examine the causal factors so could be useful for develop preventing program. This study aimed to analyze the relationship between teenager’s and parent’s characteristics, parent-child communication, and self-control; and cyberbullying among teenager who become junior high school students. This research used cross-sectional study design and was conducted in one of junior high school in Bogor city. The 81 students were chosen by convenience sampling for becoming participants. Data were collected by self-administered in measuring teenager’s perceive on parent-child communication and also measuring self-control and cyberbullying. The results showed that the mean ± SD of index (0-100) for parents-child communication was 67,29± 12,32; teenager’s self-control was 58,96±9,93; and teenager’s cyberbullying 22,32±9,72. Correlation test results showed there was a significant negative relationship between parents-child communication, teenager’s self-control and cyberbullying among teenagers. The results of this study indicates the importance of family and individual factors in reducing cyberbullying in junior high school students.